Sequential sampling of Aphis gossypii Glover (Hemiptera: Aphididae) and Frankliniella schultzei Trybom (Thysanoptera: Thripidae) on cotton crop - Fernandes,MG (2011)
The goal of this research was to use the sequential probability ratio test to establish a sequential sampling plan for Aphis gossypii Glover and Frankliniella schultzei Trybom infesting cotton. Field work was conducted at the agricultural experimental station of the Universidade Federal da Grande Dourados during the 2003/2004 and 2004/2005 agricultural years. Aphid colonies and individual thrips in the sampling area were counted and their numbers were recorded. The spatial distribution pattern of A. gossypii and F. schultzei in the cotton culture was aggregated. Sequential sampling plans were developed for aphids and thrips with type I and type II errors set at 0.1, common Kc = 0.6081 (aphids) and = 0. 9449 (thrips), and safety and management levels of 20% (aphids) and 40% (thrips) of infested plants. The sampling plans resulted in two decision boundaries for each species, as follows: the upper boundary, indicating when management (population control) is recommended: S1 = 4.6546 + 0.2849n (aphids), and S1 = 3.6514 + 0.1435n (thrips); and the lower boundary, indicating when population control is not necessary: S0 = -4.6546 + 0.2849n (aphids) and S0 = - 3.6514 + 0.1435n (thrips). The highest probability of error when making a decision was 3% for aphids and 2% for thrips, respectively. The maximum number of samples required to reach a decision was 63 for aphids and 95 for thrips.